GRADIEN KARAKTERISTIK HABITAT PERAIRAN SUNGAI WAY KAMBASDI TAMAN NASIONAL WAY KAMBAS - , Itno Itoyo, Dr. Dra. Erny Poedjirahajoe, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Way Kambas river (WK) as part ofWKNP which has an important role to provide water for the wildlife animal. Land use around of the upstream flow such settlements, agriculture, plantation, farm and processing tapioca flour industries affect its water quality. Habitat characteristics of WK river need to be known to obtain information about its status, so that more effective management efforts. The research aims to: 1) determine the habitat characteristics of river. 2) assess the gradient characteristics of habitat river. 3) determine the relationship between the variables of characteristics with the plankton and benthos. 4) determine the effect of the distance source of pollution with characteristics habitat. This research was conducted at the WK river flowing in the region WKNP with a length of 40 km. Placement sample is done in a systematic, a total of 12 observation points with the distance between the observation point 4 km. Sampling was carried out for 2 (two) replications. Parameters measured the temperature, salinity, total Disolved Suspend (TDS), pH (acidity), turbidity, conductivity, Biological Oxygen Disolved (BOD), Disolved Oxygen (DO), Total Suspended Solid (TSS), Chemical Oxygen Disolved (COD), Ammonia (NH3-N), phosphate, MBAs, MPN-Germs. Analysis of water quality by comparing the quality criteria grade 1 to Regulation No. 82/2001, the analysis of plankton and benthos to gain dominance, diversity and equality. Statistical analysis used the ANOVA, test comparison of two observations, correlation and regression single and multiple. The results showed that the average quality of the physics and chemistry first and second replicates are temperature (27,6oC and 26,5oC), salinity (79,2 ppm and 56,6 ppm), TDS (113,1 mg / L and 28,3 mg / L), pH (6,5 and 7), turbidity (82,5 cm and 46,5 cm), conductivity (179,67 microseconds / cm and 41,11 microseconds/cm), BOD (1,725 mg / L and 1,55 mg / L), DO (4,0 mg / L and 3,86 mg / L), TSS (21,5 mg / L and 14,3 mg / L), COD (11,0 mg / L and 17,2 mg / L), NH3-N (0,06 mg / L and 0,123 mg / L), phosphate (0,026 mg / L and 0,038 mg / L), MBAS (0,395 mg / L and 2,150 mg / L), MPN-Germs (186,25 MPN / 100 ml and 741,33 MPN / 100 ml). According to PP 82/2001 variable quality beyond that threshold BOD, DO, COD, NH3- N. Average of the first and second replicates species, number, dominance, diversity, similarity plankton are (31,17